Estresse, ansiedade e qualidade de vida em professores: efeitos do relaxamento progressivo - Freitas, Geisa Rodrigues de [UNESP] (2015)
Studies with public shocol teachers report symptoms of stress, anxiety and low life quality of these professionals, but few had intervention proposals. From this gap, the aim of this study was to investigate the effects of Jacobson's Progressive Relaxation adapted by Sandor in stress measures, anxiety and Quality of Life of public school teachers. This study smaple comprised 105 teachers from Brazil's public schools in their teaching activities. Exclusion criteria were: presence of pyschiatric diagnoses, pregnancy, being in removal of the activities as a teacher, or have less than one year working in this function. The sample was divided into three groups: intervention (G1), lecture (G2) and passage of time (G3). To stress measures, we used the ISSL and the EVENT; Quality of Life was measured using the instrumetn proposed by the World Helth Organizations. WHOQOL-bref, to measure anxiety, we used the Beck Anxiety Inventory (BAI). The data were summarized quantitatively by means of the functions of descriptive statistics; ANOVA was used for inferential analysis and comparison of more than two means. Significant improvement was found (p=0.004) in the post-test for stress measurement with ISSL. There have improvements in the perception of job stress and anxiety in the post-test for the G1, not statistically significant, however, clearly indicating a trend towards improvement compared the results with G2 and G3. The measure of quality of life in the sample were consistent with those described in the literature and the valuation difference between the three groups in the pre and post-test was not statistically significant. It is, therefore, there was a significant change in stress symptoms presented to the participants and the G1, the measures of anxiety and vulnerability of the participants before occupational stressors has been identified trend to improvement compared with the results of G2 and G3. It was found that comparing pre and...